Green Entrepreneurial Intention : The Role of Entrepreneurship Education and Entrepreneurial Self Efficacy - Rahmanto, Andi Adam; Siswandari, Siswandari; Sangka, Khresna Bayu (LPPM Universitas Pendidikan Mandalika, 2024)
The purpose of this research is to examine how entrepreneurial self-efficacy functions as a mediator in the relationship between green entrepreneurial intention and entrepreneurship education. This research used a survey method with a quantitative approach. A proportionate stratified random sampling method was utilized to calculate the sample for this study, resulting in 305 respondents from various undergraduate programs at Universitas Sebelas Maret and Universitas Negeri Semarang. This study uses data collection techniques using a closed questionnaire in the form of a Likert scale with five alternative answers. IBM SPSS Statistic 26 software was utilized in this work as a statistical analysis tool to examine the mediation effect using route analysis. The study's findings suggest that students' intentions to pursue green entrepreneurship can be influenced by entrepreneurship education, with entrepreneurial self-efficacy acting as a mediator. In order to boost students' entrepreneurial ambitions, university policymakers must incorporate entrepreneurship instruction within the curriculum. Universities should include material on green entrepreneurship in their programs to prepare students to face environmental challenges through business. In addition, it is important to develop training programs that focus on increasing confidence in entrepreneurship, such as through business simulation and mentoring. Policymakers also need to support entrepreneurship education programs that promote sustainable business by providing financial support and supportive policies.